2010
DOI: 10.1038/ajh.2009.252
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Myocardial Repolarization Lability and Arterial Baroreflex Dysfunction in Healthy Individuals With Nondipping Blood Pressure Pattern

Abstract: A nondipping BP pattern in healthy subjects is associated with elevated myocardial repolarization lability and impaired baroreflex function, suggesting dysfunction of the autonomic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…These increased BP levels parallel the reported increase in HR of BACHD mice also measured during the day [16], suggesting a global dysregulation of the cardiovascular system causing it to be hyperactive during the rest period. The blunted depression in BP levels during rest would be similar to a nondipping pressure profile observed in humans, which in many cases is an indication of dysautonomia [22] [23]. Nondippers have a higher risk for future cardiovascular events, as well as damage to other organs [23] [24].…”
Section: Discussionmentioning
confidence: 62%
“…These increased BP levels parallel the reported increase in HR of BACHD mice also measured during the day [16], suggesting a global dysregulation of the cardiovascular system causing it to be hyperactive during the rest period. The blunted depression in BP levels during rest would be similar to a nondipping pressure profile observed in humans, which in many cases is an indication of dysautonomia [22] [23]. Nondippers have a higher risk for future cardiovascular events, as well as damage to other organs [23] [24].…”
Section: Discussionmentioning
confidence: 62%
“…Speculations include nocturnal autonomic imbalance favoring sympathetic overactivity, 26 altered baroreceptor sensitivity, 26,27 increased liability of myocardial repolarization, 27 increased salt sensitivity or renal dysfunction, with nocturnal volume overload needing higher nighttime BPs to sustain natriuresis, 21,28 the presence of sleep-disordered breathing conditions or poor sleep quality, 8,29 hyperaldosteronism status, 30 increased arterial stiffness, 31 chronic low-grade inflammation and endothelial dysfunction, 32,33 and daytime orthostatic hypotension. 25,34 On the other hand, the physiopathological mechanisms underlying the possible differential prognostic effect of extreme dipping pattern according to antihypertensive status are completely unexplored, but we may speculate that it might involve orthostatic hypertension, exaggerated morning BP surge, increased BP variability, or increased arterial stiffness in extreme dippers, 24,35,36 which may partially be attenuated by antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Hoshide et al studied 74 community-dwelling Japanese normotensives and showed that atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP) and LVMI were increased in non-dippers compared with dippers. 10 An increase in these parameters is established evidence of cardiac remodeling and left ventricular hypertrophy, which sig- Data are mean ± SD or n(%).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In patients with normal blood pressure, NDP can also lead to end organ damage as seen on echocardiography, bio-inflammatory markers and microalbuminuria. [10][11][12][13] In a prospective study of individuals with normal 24-hr blood pressure, a 5% decrease in the nocturnal decline in diastolic blood pressure was significantly associated with a 20% increase in cardiovascular mortality risk. 14 Several studies have demonstrated that NDP is more common in Black hypertensives compared with other races.…”
Section: Introductionmentioning
confidence: 99%